EKSISTENSI SERIKAT PEKERJA/SERIKAT BURUH DALAM UPAYA MENSEJAHTERAKAN PEKERJA - Zulkarnain Ibrahim (Jurnal Media Hukum, 2016)
The exsistence of Labour Union do not implement the mandate of Laws. No. 21 year 2000 about Labour Union, also in covering, defensing the right/obligation of workers, and welfare of workers and their family. Informal workers not yet and should become the member of Labour Union, because they become the Indonesia’s economic strength/endurance. So that Labour Union convince goverment to help with technical guidance, management, and banking with low interest. General obstacle of Labour Union, weak in leadership’s quality and bargaining with businessmen. The personal/group needs, become the reason of fragmentation from time to time, and the vision/mission has not yet maximally executed to facing the future. The Labour Union should execute right/obligation from laws, making the members become professional in their fields, and harmonic with members and also bussinesmen.